2020
DOI: 10.5194/acp-2020-51
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular understanding of the suppression of new-particle formation by isoprene

Abstract: Abstract. Nucleation of atmospheric vapors produces more than half of global cloud condensation nuclei and so has an important influence on climate. Recent studies show that monoterpene (C10H16) oxidation yields highly-oxygenated products that can nucleate with or without sulfuric acid. Monoterpenes are emitted mainly by trees, frequently together with isoprene (C5H8), which has the highest global emission of all organic vapors. Previous studies have shown that isoprene suppresses new-particle formatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 42 publications
(81 reference statements)
3
8
1
Order By: Relevance
“…At low temperatures (blue data), the uncertainty in autoxidation temperature dependence has the greatest effect, while at high temperatures this feature is muted. The increase in yield with temperature is in qualitative agreement with observation (Quéléver et al, 2019;Simon et al, 2020).…”
Section: Hom Yield Variation With Temperature and No Xsupporting
confidence: 90%
See 3 more Smart Citations
“…At low temperatures (blue data), the uncertainty in autoxidation temperature dependence has the greatest effect, while at high temperatures this feature is muted. The increase in yield with temperature is in qualitative agreement with observation (Quéléver et al, 2019;Simon et al, 2020).…”
Section: Hom Yield Variation With Temperature and No Xsupporting
confidence: 90%
“…All HOMs were treated as being equally proficient at nucleating new particles, in agreement with the approach and nucleation rates used by Kirkby et al (2016) and Gordon et al (2017). Recent work by Heinritzi et al (2020) suggests that 20-carbon accretion products may be better at nucleating new particles, and therefore the results presented are likely to be an upper bound although nevertheless informative. Representing the different nucleation efficiencies of different HOM species will be investigated in future work.…”
Section: Nucleation Ratesmentioning
confidence: 58%
See 2 more Smart Citations
“…Recent studies have found that ions and iodine‐containing species also play important roles in nucleation processes (Jokinen et al., 2018; Kirkby et al., 2011, 2016; Kürten et al., 2016; Sipilä et al., 2016). On the other hand, biogenic hydrocarbon such as isoprene was found to suppress NPF, though currently the mechanism is still not fully understood (Heinritzi et al., 2020; Kanawade et al., 2011; Kiendler‐Scharr et al., 2012; McFiggans et al., 2019). Furthermore, NPF can be suppressed under high NO x conditions, particularly in urban atmosphere (Wildt et al., 2014).…”
Section: Introductionmentioning
confidence: 99%